Intermediate Repeat Expansion in the IATXN2/I Gene as a Risk Factor in the ALS and FTD Spanish Population - Borrego-Hernández, Daniel; Vázquez-Costa, Juan Francisco; Domínguez-Rubio, Raúl; Expósito-Blázquez, Laura; Aller, Elena; Padró-Miquel, Ariadna; García-Casanova, Pilar; Colomina, María J; Martín-Arriscado, Cristina; Osta, Rosario; Cordero-Vázquez, Pilar; Esteban-Pérez, Jesús; et al. (Biomedicines, 2024)
Intermediate CAG expansions in the gene ataxin-2 (ATXN2) are a known risk factor for ALS, but little is known about their role in FTD risk. Moreover, their contribution to the risk and phenotype of patients might vary in populations with different genetic backgrounds. The aim of this study was to assess the relationship of intermediate CAG expansions in ATXN2 with the risk and phenotype of ALS and FTD in the Spanish population. Repeat-primed PCR was performed in 620 ALS and 137 FTD patients in three referral centers in Spain to determine the exact number of CAG repeats. In our cohort, ≥27 CAG repeats in ATXN2 were associated with a higher risk of developing ALS (odds ratio [OR] = 2.666 [1.471–4.882]; p = 0.0013) but not FTD (odds ratio [OR] = 1.446 [0.558–3.574]; p = 0.44). Moreover, ALS patients with ≥27 CAG repeats in ATXN2 showed a shorter survival rate compared to those with <27 repeats (hazard ratio [HR] 1.74 [1.18, 2.56], p = 0.005), more frequent limb onset (odds ratio [OR] = 2.34 [1.093–4.936]; p = 0.028) and a family history of ALS (odds ratio [OR] = 2.538 [1.375–4.634]; p = 0.002). Intermediate CAG expansions of ≥27 repeats in ATXN2 are associated with ALS risk but not with FTD in the Spanish population. ALS patients carrying an intermediate expansion in ATXN2 show more frequent limb onset but a worse prognosis than those without expansions. In patients carrying C9orf72 expansions, the intermediate ATXN2 expansion might increase the penetrance and modify the phenotype.